2021
DOI: 10.1123/jpah.2020-0839
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Household Socioeconomic Status, Car Ownership, Physical Activity, and Cardiorespiratory Fitness in South African Primary Schoolchildren Living in Marginalized Communities

Abstract: Background: Little is known whether physical activity (PA)-promoting environments are equally accessible to children with divergent socioeconomic status (SES) in low-/middle-income countries. The authors, therefore, examined whether South African children from poorer versus wealthier families living in marginalized communities differed in moderate to vigorous PA and cardiorespiratory fitness. We also tested associations between family car ownership and PA/cardiorespiratory fitness. Methods: Parents/guardians o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The result suggests that children from low socioeconomic background participate in activities that promotes active lifestyles. In a study by Gerber et al among the marginalised black communities of South Africa, they found that children of the lowest SES accumulated higher levels of device-based moderate to vigorous PA, and that peers from the highest SES engaged in more sedentary behaviours [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result suggests that children from low socioeconomic background participate in activities that promotes active lifestyles. In a study by Gerber et al among the marginalised black communities of South Africa, they found that children of the lowest SES accumulated higher levels of device-based moderate to vigorous PA, and that peers from the highest SES engaged in more sedentary behaviours [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SES was determined by calculating a wealth index generated through a PCA, with higher scores reflecting higher SES. Details about the wealth index calculation have been described elsewhere (24). All statistical analyses were carried out using SPSS Version 27 (IBM Corporation, Armonk, NY, USA) for Windows.…”
Section: Methodsmentioning
confidence: 99%
“…number of bedrooms, people per household). The items included and exact scoring to estimate SES have been described elsewhere (24). Items possessed by >95% or <5% of the sample were excluded, with the remaining items used to generate a wealth index via principal component analysis (PCA).…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%
“…All schools (quintile 3 schools) were located in peri-urban, marginalized communities. Results from this study have been published previously [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. However, the objectives articulated above have yet to be examined, and hence, the findings presented in the current publication are original.…”
Section: Methodsmentioning
confidence: 99%